VALUE RELEVANCE OF EARNINGS QUALITY AMONG INDONESIAN PUBLIC COMPANIES - Santoso, Budiman Linggo (Jurnal Ilmiah Mahasiswa FEB, 2015)
The objective of this study is to investigate value relevance of earnings quality in Indonesian public companies. This research uses price model, i.e. stock price to represent company value. Value relevance is measured by earnings per share and book value per share, while earnings quality is measured through using earnings management measurement method (abnormal cash flow from operation (Abn. CFO) and abnornal discretionary expense (Abn. DISCR)). Value relevance of earnings quality is measured by the moderation of Abn. CFO and Abn. DISCR to earnings per share and book value per share. Regression analysis on sample of 229 companies from year 2012 to 2014 is used to test the hypothesis. Samples are taken from all company sectors in Indonesia Stock Exchange (IDX). The result shows that earnings quality increases relevancy of earnings per share and book value per share. Keyword: Value relevance, earnings per share, book value per share, stock price, abnormal cash flow from operation, abnormal discretionary expense.